2021
DOI: 10.1186/s12989-021-00428-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospects on the nano-plastic particles internalization and induction of cellular response in human keratinocytes

Abstract: Background Today, cosmetic products are very popular with both men and women to improve their appearance and increase their social acceptability. Results In this study, nano-sized (30–300 nm) plastic particles were isolated from the commercial face-scrubs and treated on the human keratinocytes. The observed adherence of polyethylene nano-plastics (PENPs), polystyrene NPs (PSNPs), and face-scrubs isolated nano-plastics (NPs) on the keratin layer rev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 95 publications
1
19
0
1
Order By: Relevance
“…In this study, we consider the role that particles compatible with MPs may play in placental stress in terms of endoplasmic reticulum dilation/stressed mitochondria/oxidative stress. Numerous in vivo and in vitro studies have shown that MPs cause oxidative stress, apoptosis, inflammation, mitochondrial and lysosomal dysfunction, autophagy, and genotoxicity in various tissues (gut, intestine, liver) and cell types (human keratinocytes, human intestinal epithelial cells, gastric epithelial cells, human umbilical vein endothelial cells) [ 35 , 63 , 70 , 71 , 72 ]. Abnormal colocalization of mitochondria and endoplasmic reticulum has been also found in porcine oocytes exposed to Monobutyl phthalate (phthalates are a group of chemicals associated with PVC products as plasticizers in medical tubing, soft plastic toys, food packaging and in many personal care products) [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we consider the role that particles compatible with MPs may play in placental stress in terms of endoplasmic reticulum dilation/stressed mitochondria/oxidative stress. Numerous in vivo and in vitro studies have shown that MPs cause oxidative stress, apoptosis, inflammation, mitochondrial and lysosomal dysfunction, autophagy, and genotoxicity in various tissues (gut, intestine, liver) and cell types (human keratinocytes, human intestinal epithelial cells, gastric epithelial cells, human umbilical vein endothelial cells) [ 35 , 63 , 70 , 71 , 72 ]. Abnormal colocalization of mitochondria and endoplasmic reticulum has been also found in porcine oocytes exposed to Monobutyl phthalate (phthalates are a group of chemicals associated with PVC products as plasticizers in medical tubing, soft plastic toys, food packaging and in many personal care products) [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Balfourier et al [88] suggested that ROS production in the lysosome activated the degradation of Au NPs. The lysosomal degradation of other NMs including plastic NPs, [89] carbon nanotubes, [90] and Ag NWs [91] were also reported, but the digestion ability of lysosome appeared to be limited as few studies reported the complete degradation of NMs in the lysosome.…”
Section: The Intracellular Trafficking Of Nmsmentioning
confidence: 99%
“…While it is unknown if these compounds leak straight into living tissues, some additives like Bisphenol A have been discovered to be consumed by marine biota (Chen et al, 2020;Koelmans et al, 2014), Absorption of this leachate frequently used in lining food and beverage cans, can induce endocrine problems and adversely affect human health (Ryan, 2015). In particular, associated health risks may include, cytotoxicity (Gopinath et al, 2021), neurotoxicity (Han et al, 2021;Varsou et al, 2021), immunotoxicity, reproductive toxicity (He et al, 2021), or even carcinogenicity (Gao et al, 2021). Yip et al (2022) have tested and predicted the possibility of MNPs transfer from mother to offspring.…”
Section: On Living Organismsmentioning
confidence: 99%